An Obstructing Small Bowel Phytobezoar in an Elderly Female Nigerian: A Case Report and Literature Review. (13th June 2017) - Balogun, O. S.; Osinowo, A. O.; Afolayan, M. O.; Adesanya, A. A.
Abstract : Small bowel obstruction secondary to phytobezoars is an unusual presentation in surgery. We present a case of an elderly female patient with an insidious onset of abdominal pain, abdominal distension, and bilious vomiting diagnosed radiologically to be small bowel obstruction. Exploratory laparotomy revealed a trapped mass of vegetable matter in the distal ileum. She had enterotomy with primary closure for removal of obstructing ileal phytobezoars. Her postoperative recovery was uneventful.